Om semantiske rollers skematik - Lund, Steffen Nordahl (HERMES - Journal of Language and Communication in Business, 2017)
This paper focuses on the dynamic interrelationship between semantic roles. On the basis of a minimalistic set of roles: agent, topos, locus, and instrument, inspired by the component grammar outlined by Hanne Korzen, Henning Nølke, Henrik Prebensen and Finn Sørensen, morphological schemes of pos-sible connections between semantic roles in modern French nuclear sentences are proposed within a catastrophe theoretic framework.